2021
DOI: 10.1128/jb.00565-20
|View full text |Cite
|
Sign up to set email alerts
|

Essential Gene Analysis in Acinetobacter baumannii by High-Density Transposon Mutagenesis and CRISPR Interference

Abstract: Acinetobacter baumannii is a poorly understood bacterium capable of life-threatening infections in hospitals. Few antibiotics remain effective against this highly resistant pathogen. Developing rationally-designed antimicrobials that can target A. baumannii requires improved knowledge of the proteins that carry out essential processes allowing growth of the organism. Unfortunately, studying essential genes has been challenging using traditional techniques, which usually require time-consuming recombination-bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 67 publications
1
63
0
Order By: Relevance
“…Accordingly, Δ wza and Δ wzy mutants, but not Δ wcaJ , lead to defects in the cell envelope of the strain Kpn SGH10 [ 51 ]. In Acinetobacter baumannii , high-density transposon mutagenesis also recently revealed that inactivation of genes involved in the last steps of capsule biosynthesis is much more deleterious than those encoding the early steps [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Δ wza and Δ wzy mutants, but not Δ wcaJ , lead to defects in the cell envelope of the strain Kpn SGH10 [ 51 ]. In Acinetobacter baumannii , high-density transposon mutagenesis also recently revealed that inactivation of genes involved in the last steps of capsule biosynthesis is much more deleterious than those encoding the early steps [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used CRISPRi (25) to validate the negative genetic interactions between elsL and the strongest hits within each pathway ( ldt Ab , RS13190-zapA, blhA , and mlaC-F ). Chimeric single guide RNAs (sgRNAs) were designed to target the 5’ end of each locus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CRISPRi allows efficient knockdown of operons (26); RS13190-zapA and mlaC-F are therefore each likely to be co-repressed in this strategy. The effect of knockdown on colony growth was compared with two parallel controls—(1) growth in the absence of dCas9 inducer (-aTc), and (2) growth with a control, non-targeting sgRNA (25). CRISPRi of each locus in the WT strain resulted in colony growth that was at or near control levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations